Closed Genome Sequence of Phytopathogen Biocontrol Agent Bacillus velezensis Strain AGVL-005, Isolated from Soybean - Pylro, Victor Satler; Franco Dias, Armando Cavalcante; Andreote, Fernando Dini; Morais, Daniel Kumazawa; Varani, Alessandro de Mello [UNESP]; Fasanella Andreote, Cristiane Cipolla; Almeida Bernardo, Eduardo Roberto de; Zucchi, Tiago (Amer Soc Microbiology, 2018)
We report here the closed and near-complete genome sequence and annotation of Bacillus velezensis strain AGVL-005, a bacterium isolated from soybean seeds in Brazil and used for phytopathogen biocontrol.